Na temat studiów nad kaflarstwem i urządzeniami grzewczymi słów kilka - Dąbrowska, Maria (Acta Universitatis Lodziensis. Folia Archaeologica, 2010)
Tiles, components of stoves, were relatively late included within the domain of archaeologists’ interest. First studies were prepared by historians of art, who concentrated mainly on so-called artistic craft. The intensity of archaeological researches on the Middle Ages and modern times as well as parallel developing studies on material culture and living conditions of dwellers of Polish territory directed archaeologists’ interests towards problems of preservation against cold. In the area of interests there were such devices as fireplaces, heating of hypocaustum type, stoves and kitchen ranges. On estimating twenty years of studies on tiles it should be stated that most of initially put forward problems were taken up by researchers, and the obtained results are satisfactory. One of more important tasks was precise dating of tiles. The basis for chronology determination remained an analysis of stylistic features of decorative motifs. Equally important and stating the dating precisely are written relations connected with investigated object as well as other material sources, which make cultural context of the analyzed layers. Hitherto, the answer to the question about the genesis of a phenomenon, which was an introduction of stoves to Poland and their eastward expansion was not obtained. The necessity of assessment whether centres specializing in production of these products existed is connected with this problem. Another task is continuation of research on pottery raw materials – clear distinguishers of tiles produced in a given region. The present volume is a consequence of a series of so-called Tile workshops initiated and organized by the Museum of the Origins of the Polish State in Gniezno and by the Polish Archaeologists’ Scientific Association in Poznań. Papers included in the volume present results of research conducted not only on tiles but also on broadly understood issues connected with heating of dwelling interiors.